Epitaxial Growth of Germanium on Silicon for Light Emitters - Chengzhao Chen; Cheng Li; Shihao Huang; Yuanyu Zheng; Hongkai Lai; Songyan Chen (International Journal of Photoenergy)
This paper describes the role of Ge as an enabler for light emitters on a Si platform. In spite of the large lattice mismatch of ~4.2% between Ge and Si, high-quality Ge layers can be epitaxially grown on Si by ultrahigh-vacuum chemical vapor deposition. Applications of the Ge layers to near-infrared light emitters with various structures are reviewed, including the tensile-strained Ge epilayer, the Ge epilayer with a delta-doping SiGe layer, and the Ge/SiGe multiple quantum wells on Si. The fundamentals of photoluminescence physics in the different Ge structures are discussed briefly.